Influence of catheter orientation on local impedance parameters during radiofrequency delivery in AF ablation. (19th May 2022) - Schillaci, V; De Sanctis, V; Mazza, A; Zucchelli, G; Notaristefano, F; Gagliardi, M; Meynet, I; Mantica, M; Solimene, F; Anselmino, M; Stabile, G; Ottaviano, L; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Recently, a novel contact force (CF) sensing catheter able to measure local tissue impedance (LI) providing a measure of tissue characteristics has become available for clinical use. Purpose: We sought to evaluate the influence of catheter contact angle on LI and CF parameters in consecutive atrial fibrillation ablation cases. Methods: Consecutive pts undergoing radiofrequency catheter (RFC) ablation of AF from the CHARISMA registry were included. A novel ablation catheter (IntellaNav Stablepoint catheter) with dedicated algorithm (DirectSense) was used to measure LI at the distal electrode of this catheter. Each targeted spot was characterized in terms of RF delivery time, catheter contact angle, baseline LI and subsequent LI drop during ablation at different levels of CF (<5g, 5-19g and ≥20g). RFC ablations were performed at ≥45 watts. Data are reported as mean±SD. Results: A total of 4193 point ablations performed around PVs from 54 cases of AF ablation were analyzed (57% paroxysmal, 85% de novo). The LI was 157±17Ω prior to ablation and 137±14Ω after ablation (p<0.0001, absolute LI drop of 22±8Ω). The CF was 12.5±8g and the RFC delivery time was 8.8±4s. The LI drop increased as CF increased (ranging from 18.9±7Ω for CF<5g to 24.8±7Ω for CF≥20g, p<0.0001) as well as RFC delivery time decreased (ranging from 12.7±4s for CF<5g to 6.6±4s for CF≥20g, p<0.0001). The LI drop at perpendicular orientations was significantly lower than at parallel orientations (19.5±8Ω vs 23.4±8Ω, p<0.0001) and RFC delivery time was higher (9.6±5s vs 8.4±4s, p<0.0001). This trend was confirmed among different level of CF both for LI drop and RFC delivery time. Figure Conclusions: In this experience, the magnitude of the LI drop at perpendicular orientation were significantly lower than at parallel orientation and RFC delivery time was greater in parallel instances than in perpendicular instances. Thus, perpendicular RF ablations required longer RF applications and produced weaker LI decreases that parallel lesions, suggesting that catheter orientation may have critical role in RF delivery for ablation.